Design and evaluation of an actuated exoskeleton for examining motor control in stroke thumb. (1st February 2016) - Wang, Furui; Jones, Christopher L.; Shastri, Milind; Qian, Kai; Kamper, Derek G.; Sarkar, Nilanjan
Abstract : Chronic hand impairment is common following stroke. This paper presents an actuated thumb exoskeleton (ATX) to facilitate research in examining motor control and hand rehabilitation. The ATX presented in this work aims to provide independent bi-directional actuation in each of the 5 degrees of freedom (DOF) of the thumb using a novel flexible shaft-based mechanism that has 5 active DOF and 3 passive DOF. A prototype has been built and experiments have been conducted to measure the allowable workspace at the thumb and evaluate the kinematic and kinetic performance of the ATX. The experimental results show that the ATX is able to provide individual actuation at all five thumb joints with high joint velocity and torque capacities. Further improvement and future work are discussed. Abstract :